The Blackwell companion to the study of religion - Segal, Robert Alan (Blackwell companions to religion., 2006)
This prestigious Companion offers the most comprehensive survey to date of the study of religion. Featuring a team of international contributors, and edited by one of the most widely respected scholars in the field, The Blackwell Companion to the Study of Religion provides an interdisciplinary and authoritative guide to the subject. Examines the main approaches to the study of religion: anthropology, the comparative method, economics, literature, philosophy, psychology, sociology, and theology. Also covers a diverse range of topical issues, such as the body, fundamentalism, magic, and new reli.